201 - LEARNING TO TEACH: THE INTRODUCTION OF PEDIATRIC ONCOLOGY IN THE TEACHING OF THE MASTER'S PROGRAM IN NURSING AT UFRN (Fiep Bulletin - online, 2011)
This article reports the nursing master students' experience after the short practice of teaching pediatric oncology, and participation in the discipline "Nursing in the children and adolescent care" where was developed activities of practice teaching-learning in Pediatric Oncology. This paper aims to discuss the facilities and difficulties occurred during the planning and management of these lessons and reflect on the contributions for the nursing master students' apprehension of how to teach. It was addressed in this work the practice in teaching and the contributions to teaching-learning for integration between undergraduate and graduate students.
Keywords: Learning; education; nursing